Hyperexcitability in Cultured Cortical Neuron Networks from the G93A-SOD1 Amyotrophic Lateral Sclerosis Model Mouse and its Molecular Correlates. (15th September 2019) - Marcuzzo, Stefania; Terragni, Benedetta; Bonanno, Silvia; Isaia, Davide; Cavalcante, Paola; Cappelletti, Cristina; Ciusani, Emilio; Rizzo, Ambra; Regalia, Giulia; Yoshimura, Natsue; Ugolini, Giovanni Stefano; Rasponi, Marco; et al.
Abstract: Amyotrophic lateral sclerosis (ALS) is a neurodegenerative disease affecting the corticospinal tract and leading to motor neuron death. According to a recent study, magnetic resonance imaging-visible changes suggestive of neurodegeneration seem absent in the motor cortex of G93A-SOD1 ALS mice. However, it has not yet been ascertained whether the cortical neural activity is intact, or alterations are present, perhaps even from an early stage. Here, cortical neurons from this model were isolated at post-natal day 1 and cultured on multielectrode arrays. Their activity was studied with a comprehensive pool of neurophysiological analyses probing excitability, criticality and network architecture, alongside immunocytochemistry and molecular investigations. Significant hyperexcitability was visible through increased network firing rate and bursting, whereas topological changes in the synchronization patterns were apparently absent. The number of dendritic spines was increased, accompanied by elevated transcriptional levels of the DLG4 gene, NMDA receptor 1 and the early pro-apoptotic APAF1 gene. The extracellular Na +, Ca 2+, K + and Cl − concentrations were elevated, pointing to perturbations in the culture micro-environment. Our findings highlight remarkable early changes in ALS cortical neuron activity and physiology. These changes suggest that the causative factors of hyperexcitability and associated toxicity could become established much earlier than the appearance of disease symptoms, with implications for the discovery of new hypothetical therapeutic targets. Highlights: Spontaneous activity in cultured G93A-SOD1 cortical neurons shows hyperexcitability. G93A-SOD1 neurons present an increased number of dendritic spines. The DLG4 gene, encoding PSD-95, is overexpressed in G93A-SOD1 neurons. The NMDA receptor 1 is overexpressed in G93A-SOD1 neurons. The early pro-apoptotic APAF1 gene is overexpressed in G93A-SOD1 neurons.